PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH (Studi Deskriptif Kec. Curup Tengah, Kab. Rejang Lebong, Bengkulu) - Bayu Panji Aji (UNIVED Press, Universitas Dehasen Bengkulu, 2016)
The increasing rate of population growth and economic development occurring in the Curup Tengah District, Kab. Rejang Lebong, Bengkulu has led to the increasing waste generated. This can lead to declining environmental quality in the region, especially the situation is aggravated by inadequate handling and waste management systems are implemented by the Regional Government. Therefore, the required real effort in resolving the existing problems of waste such as by increasing community participation in waste management. This study aims to determine how community participation in waste management in the Curup Tengah District. This participation may take the form pasrtisipasi community in local government policy decisions about waste management. Pasrtisipasi other forms of society can be seen by taking out the trash in the space provided, do not throw garbage in open dumps, as well as by not burning waste not in accordance with the technical requirements for waste management. Results of analysis showed that public participation in policy-local government on waste management in the Curup Tengah District, Kab. Rejang Lebong, Bengkulu was well with the average value of respondents' answers to the questionnaire was 3.83, Participation of the community by removing trash in places that have been prescribed or provided in the Curup Tengah District, Kab. Rejang Lebong, Bengkulu was well with the average value of respondents' answers to the questionnaire was 3.91, with community participation does not throw garbage in the open field in the Curup Tengah District, Kab. Rejang Lebong, Bengkulu was well with the average value of respondents' answers to the questionnaire is 3.77, and the participation of the community by not burning waste not in accordance with technical requirements for waste management in the Curup Tengah District, Kab. Rejang Lebong, Bengkulu was well with the average value of respondents' answers to the questionnaire was 3.69. This shows that the general public's Participation in the Waste Management at Curup Tengah District, Kab. Rejang Lebong, Bengkulu was well with the average value of the respondent's answer was 3.8. Keywords: participation, community, garbage